Understanding oral stereotypies in calves: alternative strategies, hypothalamic–pituitary–adrenal axis (re)activity and gene by environment interactions. (8th November 2016) - Webb, L. E; van Reenen, C. G; Engel, B; Berends, H; Gerrits, W. J. J; Bokkers, E. A. M
Abstract : Stereotypies are used as indicators of poor animal welfare and it is, therefore, important to understand underlying factors mediating their development. In calves, two oral stereotypies, that is, tongue playing and object manipulation, result mostly from insufficient structure in the diet. Three hypotheses were studied: (1) oral stereotypies in calves are one of two alternative strategies, the alternative being hypo-activity; (2) stereotyping and non-stereotyping calves differ in terms of cortisol secretion; (3) oral stereotypy development in calves rests on a gene by environment interaction. Eight-week-old bull calves ( n =48) were assigned to one of four solid feed allowances (0, 9, 18 or 27 g dry matter/kg metabolic weight per day) with the following composition: 50% concentrate, 25% maize silage and 25% straw on dry matter basis. The calves received milk replacer in buckets, the provision of which was adjusted to achieve equal growth rates. At 14 to 18 weeks of age, calves were exposed to a challenge, that is, tethering inside cages. Oral stereotypies and inactivity were recorded in the home pens in the 4 weeks before the challenge using instantaneous scan sampling. Salivary cortisol levels were measured at −120, +40, +80, +120 min and +48 h relative to the challenge. Individual differences in behaviour were recorded in the first 30 min after challenge implementation using focal animal sampling and continuous recording, and these elements were entered into a principal component (PC) analysis to extract PCs. Regression analyses were performed to find relationships between stereotypies and inactivity, stereotypies and cortisol, and stereotypies and PCs (individual differences, genes) and solid feed (environment). Relationships between PCs and cortisol were also investigated to help with the interpretation of PCs. Hypotheses 1 and 2 were rejected. Hypothesis 3, however, was supported: calves with a zero solid feed allowance, that is, in the most barren environment, showed links between stereotypies and two of the PCs. Calves that displayed high levels of idle and rapid locomotion and low levels of oral contact with the cage during the challenge also displayed high levels of object manipulation in the home pens. Calves that displayed low levels of stepping and turning attempts during the challenge also displayed high levels of tongue playing in the home pens. This study corroborates the gene by environment interaction on the development of oral stereotypies in calves.